Pengaruh Asimetri Informasi, Manajemen Laba, dan Pengungkapan Modal Intelektual Terhadap Biaya Ekuitas Studi Empiris Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017 – 2021 - Elita Nuraini; Listiya Ike Purnomo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to obtain empirical evidence regarding the influence of information asymmetry, earnings management, and intellectual capital disclosure on the cost of equity. This type of research is quantitative research. The population in this study are pharmaceutical sector companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The sampling technique used in this research was obtained using the purposive sampling method. The population in this study was 12 companies and 9 companies met the sample criteria. The analytical method used in this research is panel data regression analysis assisted by the Eviews 12 application. The results of this research show that information asymmetry, earnings management and intellectual capital disclosure simultaneously influence the cost of equity. Information asymmetry and earnings management have no effect on the cost of equity, while the value of intellectual capital disclosure has an effect on the cost of equity. Keywords: cost of equity; information asymmetry; profit management; disclosure of intellectual capital